1998
DOI: 10.1089/jir.1998.18.963
|View full text |Cite
|
Sign up to set email alerts
|

Serum Intercellular Adhesion Molecule-1 and Long-Term Response to IFN-α2b Therapy in Chronic Hepatitis C

Abstract: We have attempted to correlate the outcome of interferon (IFN) therapy with circulating soluble intercellular adhesion molecule-1 (sICAM-1) and the level of viremia in a sample of patients with chronic hepatitis C virus (HCV) infection. Forty-two patients were studied. Eighteen patients were maintained in long-term remission following IFN therapy, whereas 24 did not respond or relapsed. Serum concentrations of sICAM-1 were measured by enzyme-linked immunoassay. Viremia was measured by branched DNA signal ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
3
1
1
Order By: Relevance
“…1). Furthermore, in contrast with the observations of Baguasco et al, 11 who noted higher basal pretreatment ICAM-1 levels in responders to therapy, compared with non-responders, in our patients pretreatment levels in responders and non-responders did not differ significantly.…”
Section: Discussioncontrasting
confidence: 99%
“…1). Furthermore, in contrast with the observations of Baguasco et al, 11 who noted higher basal pretreatment ICAM-1 levels in responders to therapy, compared with non-responders, in our patients pretreatment levels in responders and non-responders did not differ significantly.…”
Section: Discussioncontrasting
confidence: 99%
“…Therapy with ·-IFN led to a marked decrease in serum ICAM-1 concentrations in both groups, but only in ETR patients. This result is in agreement with other reports in the literature [10][11][12][13][14][15][16][17][18] and suggests that ·-IFN is efficacious because it reduces immuno-cell activation and the inflammatory processes.…”
Section: Discussionsupporting
confidence: 93%
“…This expression favours the adhesion of T lymphocytes with surface lymphocyte functionassociated antigen-1 on hepatocytes and may trigger an immune reaction and maintain chronic inflammation [5,6]. Elevated serum levels of a soluble form of ICAM-1 (sICAM-1) have been reported in patients with chronic liver disease of alcoholic [7], autoimmune [8,9] and viral etiology, particularly hepatitis C virus (HCV), as well as changes in these levels after treatment with ·-IFN [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Then, our findings appear in agreement with literature data and suggest that VCAM-1, which is considered to reflect the degree of liver fibrosis (25,28) and ICAM-1 levels, markers of liver inflammation, have significantly decreased in HCV patients with normal ALT levels following interferon administration (28,42,46,47). However, the relationship between ICAM-1, VCAM-1 and ALT values does not implicate a direct involvement of these adhesion molecules in physiopathology of hepatocellular damage, but it could only reflect the activation of undergoing immunological mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…While, elevated serum VCAM-1 in chronic hepatitis have been reported by some authors (39,40). Also, many authors confirmed our data related to higher levels of sICAM-1 among patients with chronic HCV-related hepatitis than do control subjects (28,41,42). Moreover, similar results are reported in patients with CLD (34) and CHC (18,25).…”
Section: Discussionsupporting
confidence: 88%